Rental houses: History and contemporaneity - Solodilova, Lyubov (project baikal, 2021)
The topic of housing efficiency has always been among the priorities since the emergence of rental houses. However, in today's Russia, a multi-apartment residential building with collective forms of property is widely spread, which is a low-efficiency housing facility and definitely needs infrastructural improvement within the framework of the public-private entrepreneurship. The basis for this is the efforts of government agencies, which more and more often enter the rental housing market, creating competition for the shadow sector of rented apartments.
Keywords: architecture; rental houses; renting of apartments; economic efficiency and management